Inductive and non-inductive load tests on type ATB - form E General Electric Co. alternator - Harold, William H.; Burt, Harvy Anson; Fulton, Robert Anson (My University, 1905)
Introduction: The generator tested for characteristic action under different load conditions is of the revolving field, separately excited, stationary armature type. The above drawing shows the principal points in the construction of the machine. On the left is the main pulley which is run by the main drive belt; on the right is a smaller one from which a small direct current generator is run for exciting the alternator field. The shaft is lubricated by rings which dip into an oil reservoir. The revolving field receives its exciting current from the exciter through two slip rings. The field spider and pole faces are of laminated steel that in the pole faces is japanned and that in the spider is not. These laminations are held together by bolts as shown in drawing. The armature ring is built of japanned laminations which are held together by bolts and clamps. If the laminations should for any reason become loose and cause a disagreeable humming they may readily be tightened. There are six field coils which are wound as shown; all coils are in series each adjacent one being wound opposite and the terminals brought to the slip rings. One brush on the ring is shown; there are two brushes on each ring. The scheme of an armature slot is shown on drawing and is the construction most commonly employed by modern dynamo builders
Citation: Harold, William H., Burt, Harvy Anson, and Fulton, Robert Anson. Inductive and non-inductive load tests on type ATB - form E General Electric Co. alternator. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Theory of Alternators; Saturation Curves; Synchronous Impedance; Theses